2008
DOI: 10.1007/s10485-007-9120-5
|View full text |Cite
|
Sign up to set email alerts
|

Epicompletion in Frames with Skeletal Maps, II: Compact Normal Joinfit Frames

Abstract: An epireflection ψ is constructed of the category KNArS of compact normal joinfit frames, with skeletal maps, in the subcategory SPArS consisting of strongly projectable KNArS-objects. The construction is achieved via a pushout in the category FrmS of frames with skeletal maps, and involves rather intimately the regular coreflection of the object to be reflected. Further, if the regular coreflection ρ is applied to the reflection map ψ A : A −→ ψ A one obtains the extension of ρ A to its absolute.Keywords Epir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 15 publications
(16 reference statements)
0
15
0
Order By: Relevance
“…This article is the continuation of the work recorded in [11,14,15]. The first paper showed that the passage from a compact regular frame A to its absolute ε A is functorial if one restricts to skeletal frame homomorphisms.…”
Section: Mathematics Subject Classifications (2000) Primary 06d22 · Smentioning
confidence: 70%
See 3 more Smart Citations
“…This article is the continuation of the work recorded in [11,14,15]. The first paper showed that the passage from a compact regular frame A to its absolute ε A is functorial if one restricts to skeletal frame homomorphisms.…”
Section: Mathematics Subject Classifications (2000) Primary 06d22 · Smentioning
confidence: 70%
“…Details may be found in [15,Sections 4 and 5]. We remind the reader of the conventions set forth in Remark 1.3 on the naming of categories.…”
Section: ψ Revisitedmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work we have concentrated on the relationship between the structures of the two frames involved. Regarding the question of existence, we have made some progress on a related question, namely, the existence of a strongly projectable hull; let us refer the reader to [30].…”
Section: Definition 313mentioning
confidence: 99%